Defect Density-Dependent Dynamics of Double Absorber Layered Perovskite Solar Cell - Lakshmi Prasanna J; Ekta Goel; Amarjit Kumar (IEEE Photonics Journal)
This work elucidates the intricate interplay between the structural complexity of double absorber layered perovskite solar cells and the presence of defects, offering crucial insights for advancing the field of photovoltaics. The study systematically investigates the impact of a heterostructure featuring two perovskite absorber layers on device efficiency and highlights the challenges associated with defects. Our comprehensive analysis underscores the significance of a precisely tuned conduction band offset within the heterostructure, a parameter critical for achieving superior charge transport properties and overall device performance. Moreover, deliberate introduction of acceptor defects emerges as a strategic avenue for enhancing the structural integrity and photovoltaic output of the solar cell. This research contributes to the evolving understanding of defect engineering in perovskite solar cells, providing an intricate perspective on defect dynamics to improve device functionality. The identified parameters and insights presented in this study facilitate and guide the design and fabrication of advanced perovskite solar cells, emphasizing the importance of tailored heterostructure configurations and defect management strategies.